MOISTURE ELASTICITY OF INHOMOGENEOUS THICK-WALLED HOLLOW BALL UNDER NONSTATIONARY HUMIDITY CONDITIONS - V I Avershyev; A S Avershyev (Structural Mechanics of Engineering Constructions and Buildings, 2014)
There is presented a solution of the problem of centrally symmetric unsteady moisture transfer in a hollow spherical array, modeling part of ground mass, with the propagation of the moisture from the inner surface to periphery. At the second stage is solved quasistationary problem of moisture elasticity for heterogeneous body because of uneven changing the deformation characteristics of the soil by saturated it with moisture. The term “moisture elasticity” is used by analogy with the term thermo-elasticity since the presence of moisture in the material induce forced deformations which is similar to the temperature deformations and problems of heat and mass transfer use the same mathematics.